Volume 5: Turbo Expo 2005 2005
DOI: 10.1115/gt2005-68101
|View full text |Cite
|
Sign up to set email alerts
|

TRANSEO Code for the Dynamic Performance Simulation of Micro Gas Turbine Cycles

Abstract: In recent years microturbines and, more generally, small radial turbomachinery have been of great interest to the power industry due to their possible integration with advanced energy systems involving very high-tech components, such as high temperature fuel cells, high temperature ceramic heat exchangers and air saturators, which are still under development. Even if microturbine technology is already commercially available, when such an engine is inserted into a more complex plant there are at least two diffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 0 publications
0
48
0
Order By: Relevance
“…Although in this work the control system is completely new, the same models of [33] were considered for plant components to highlight the good performance achieved by this new control system compared to the previous one [33]. This model was developed using the TRANSEO tool [45,46], a visual, user-friendly modular program based on a library of components for off-design, transient and dynamic analyses [47] of energy systems.…”
Section: Modelmentioning
confidence: 99%
“…Although in this work the control system is completely new, the same models of [33] were considered for plant components to highlight the good performance achieved by this new control system compared to the previous one [33]. This model was developed using the TRANSEO tool [45,46], a visual, user-friendly modular program based on a library of components for off-design, transient and dynamic analyses [47] of energy systems.…”
Section: Modelmentioning
confidence: 99%
“…Using a mass inventory control scheme, Traverso et al 10 showed stable behavior of a 24-kW solar-dynamic CBC converter with heat rejection radiators subjected to orbital sink temperature periodicity. In a description of a transient code validation case, Traverso 11 also showed the importance of thermal energy storage in the turbine wheel of a commercial microturbine. Ulfsnes 12 studied the transient behavior of a semi-closed O2/CO2 gas turbine.…”
mentioning
confidence: 99%
“…This model (developed with components validated in previous works (Ghigliazza et al, 2009a;Ghigliazza et al, 2009b) was based on the simplification of simulation components (cell stack, reformer, anodic loop, off-gas burner, expander) developed in the TRANSEO tool (Traverso, 2005) of the TPG research group. Through the Real-Time Windows Target tool and the UDP interface approach it is possible to study the entire hybrid system using the model for components not physically present in the test rig.…”
Section: Fuel Cell Stack Real-time Model To Be Connected To the Rigmentioning
confidence: 99%